Contemporary Analysis of Inconsistencies Between Physician-reported Disclosures at the AAOS Annual Meeting and Industry-reported Financial Disclosures in the Open Payments Database. (6th July 2022) - Bovonratwet, Patawut; Islam, Wasif; Honig, Evan L.; Martino, Brooks M.; Chen, Aaron Z.; Albert, Todd J.; Su, Edwin P.
Abstract : Introduction: Healthcare regulators and patients are increasingly interested in financial transparency between physicians and the industry because of concerns of bias. Methods: Disclosures for every first and last author with a medical degree from the United States associated with a poster or podium presentation at the American Academy of Orthopaedic Surgeons (AAOS) 2019 Annual Meeting were identified. Author characteristics were collected. AAOS disclosures were then compared with disclosures from the Open Payments Database to determine whether any inconsistencies existed. Results: In total, 2, 503 AAOS presenters were identified, and 1, 380 authors met the inclusion criteria. Using AAOS disclosures as the standard comparator, 482 authors (35%) had an inconsistency in any category between AAOS disclosures and the Open Payments Database. Inconsistency rates for each category were 8% for royalties, 10% for speaker's fee, 15% for paid consultant, 16% for research, 14% for stocks, and 1% for other financial support. Discussion: Although the inconsistency rate for each category has improved over the years, the overall inconsistency rate between physician-reported disclosures at a recent AAOS Annual Meeting and industry-reported relationships reported in the Open Payments Database was still 35%.